Efektivitas Pengelolaan Dana Desa dalam Meningkatkan Pembangunan Desa: Studi di Desa Mendalo Indah Kecamatan Jambi Luar Kota Kabupaten Muaro Jambi - Elviyanti Anggraini; Sucipto Sucipto; Nurlia Fusfita (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This research aims to determine the effectiveness of village und management in improving the development of mendalo indah village, jambi luar kota district, muaro jambi regency. The type of research used is qualitative research. The data collection methods used are observation, interviews, and documentation. Furtherore, the research result are analyzed using the descriptive percentage ratio for the effectiveness of village fund management in the field of physical development of mendalo indah village. Meanwhile, the data analysis technique used in this research is to calculate he comparison of village fund realization with the village fund expenditure target multiplied by 100%. Based on the result of this research, the affectiveness of village fund management in improving village development in mendalo indah in 2017-2022 is the effective category. Because the level of effectiveness each year is at 90-100%